THE ROLE OF MONITORING AND EVALUATION IN THE SUCCESSFUL IMPLEMENTATION IN MUKONO DISTRICT - KIZITO GIDEON (Uganda Christian University, 2025)
This study was conducted to determine the role of monitoring and evaluation practices in the successful implementation of projects in Mukono district. The objectives of this study were to establish the extent to which data management impacts the successful implementation of projects in Mukono district, Assess the effects of communication of M&E findings on successful implementation of projects in Mukono district and Assess the impact of capacity of M&E team (staffing and finances) on the successful implementation of projects in Mukono district. This study employed a cross-sectional research design and targeted 14 respondents and a sample of 22 respondents of the target population was considered. Stratified sampling technique method was used and primary data was collected through the use of questionnaires. A pilot study was conducted to pretest the validity and reliability of instruments for data collection. The research supervisor’s opinion was obtained to ensure content validity of the research instrument. The test re-test technique was used to estimate the reliability of the instruments. Cronbach's Alpha Coefficient of values greater or equal to 0.7 will be an acceptable indicator of internal consistency. The data was analyzed using SPSS version 21 and presented using frequency tables to facilitate comparisons and conclusions. Data collected was analyzed and interpreted based on the identified independent and dependent variable. The data was analyzed using Correlation regression where the study used Spearson’s correlation to relate the variables, This was to establish if there was a correlation between dependent variable Successful project implementation against independent variable of data management and its influence to successful project implementation, communication of M&E findings and successful project implementation as well as capacity of M&E team (staffing and finances) and successful project implementation. The study revealed that strength of data management, communication of M&E findings and selection of capacity of M&E team (staffing and finance) played an important role in determining the successful implementation of projects in Mukono district. M & E is important for success of any project, yet in most projects it has not been adopted effectively. The role of data management, communication of M&E findings and capacity of M&E (staffing and finances) leaves only 24.8 percent unexplained. The P- value of 0.000 (Less than 0.05) implies that the model of M&E factors influencing project success is significant at the 95% confidence level. The researcher concluded that there is need to evaluate other factors which contribute to project success and also the capacity of M&E team should be given its due recognition to the role it plays in ensuring successful implementation of projects in Mukono district.